The Relations among Fuzzy t-Filters on Residuated Lattices - Huarong Zhang; Qingguo Li (The Scientific World Journal)
We give the simple general principle of studying the relations among fuzzy t-filters on residuated lattices. Using the general principle, we can easily determine the relations among fuzzy t-filters on different logical algebras.